Deportations of civilians from Central and Eastern European countries to labor camps of the Main Administration for Prisoners of War and Internees of the NKVD of the USSR in 1944–1945 - Golon, Mirosław (Balcanica Posnaniensia. Acta et studia, 2001)
The article addresses the issue of the mass deportation of civilians from the countries of Central and Eastern Europe to the Soviet Union during the final phase of the Second World War. The author analyzes the political and economic motives behind Soviet policy, emphasizing the close connection between deportations, the subordination of occupied countries, and the exploitation of their human resources for the reconstruction of the Soviet economy. The aim of the study is to determine the scale of the deportations, characterize the categories of individuals subjected to repression, and establish the place of these measures within Soviet policy toward Central and Eastern Europe. The research is based on NKVD archival materials, documentation from the Main Directorate for Prisoners of War and Internees, and sources concerning the functioning of the Soviet security apparatus. The analysis demonstrates that deportations were carried out under both political and economic pretexts. Those deported were classified as “internees,” “arrestees,” or “mobilized laborers.” The deportees came primarily from Germany, Poland, Hungary, Romania, and Yugoslavia, with a large proportion being of German nationality, although many Poles, Romanians, and Hungarians were also affected. The author emphasizes that these deportations became part of a second system of forced labor in the USSR, alongside the Gulag, providing the state with a source of free labor. The conclusions indicate that civilian deportations were an integral component of Soviet policies of expansion and control, serving not only security objectives but also economic exploitation and the restructuring of the political order in the region.